مساءلة التاريخ في الشعر الجزائري المعاصر - قيطون، أحمد Qitoun, Ahmed (جامعة قاصدي مرباح - ورقلة, 2014)
History permanently contained in poetry .The poet can not deny that fact and can not act without reference to its manifestations ,since it includes some shining elements that transformed reality in its diverse forms .That fact makes him be selective regarding the historical events that he feels appropriate and expressive.Past is not former events.Past is a shinning point in a dark wide space,the creative producer means that you search for the shinning point as was was written by the poet Adounis. This article deals with the fact that poetry and history function in parrallel to produce a text that reflects the conditions of the nations . I will deal at the same time with the position of the modern algerian poerty towards poetry and history and the way how they ,together,reflect the societal state.
Keywords: نقد الشعر -- الشعر العربي -- الجزائر -- العصر الحديث -- الشعراء الجزائريون -- التاريخ